2023
DOI: 10.1063/5.0153379
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty evaluation of Monte Carlo simulated line scan profiles of a critical dimension scanning electron microscope (CD-SEM)

Abstract: In recent years, precision and accuracy for a more precise critical dimension (CD) control have been required in CD measurement technology. CD distortion between the measurement by a critical dimension scanning electron microscope (CD-SEM) and a reference tool is the most important factor for a more accurate CD measurement. CD bias varies by a CD-SEM and a pattern condition. Therefore, it is urgently needed to identify, characterize, and quantify those parameters that may or may not affect the CD measurement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Finally, since our intention is to describe the hysteresis properties of Lu 1−x Sr x Cr 0.5 Fe 0.5 O 3 (x = 0 and 0.1) compounds with a qualitatively model with physical meaning parameters, we will not perform an uncertainty analysis, which is a common practice in MC modeling, see e.g. [27].…”
Section: Simulations Methodsmentioning
confidence: 99%
“…Finally, since our intention is to describe the hysteresis properties of Lu 1−x Sr x Cr 0.5 Fe 0.5 O 3 (x = 0 and 0.1) compounds with a qualitatively model with physical meaning parameters, we will not perform an uncertainty analysis, which is a common practice in MC modeling, see e.g. [27].…”
Section: Simulations Methodsmentioning
confidence: 99%
“…Villarrubia et al [34] confirmed that the MBL method can be applied to linewidth measurements down to 10 nm scale; the measurements were in good agreement with the direct observation by a transmission electron microscope. Khan et al [35] investigated the influence of the Monte Carlo model parameters on the CD determination and related theoretical uncertainties in the MBL method.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al further investigated Si nanowires with smaller linewidth scales, considering the influence of an Au substrate and electron beam parameters [43]. Khan et al studied the uncertainty of the linescan profile shapes due to physical models and electron beam parameters [44]. An ISO standard for the evaluation of linewidth by SEM has been recently established for the trapezoidal line structure in semiconductor devices [45].…”
Section: Introductionmentioning
confidence: 99%